Odpowiedzi

  • Użytkownik Zadane
2009-12-13T10:54:55+01:00
A)-18:(-1/3) = 6
b)7,5 x (-1) = -7,5
c)-2,5 x 2 1/2 = - 105/4 = - 26,25
d) 0 :(-6,8) = 0
e) -3 3/5 x (-5/6) = 3
f) -3 1/9 : (-4 2/3 ) = 31/135
2009-12-13T10:56:50+01:00
A)-18:(-1/3)= -18* -3=54
b)7,5 x (-1)= -7,5
c)-2,5 x 2 1/2 =-5/2*5/2=-25/4=-6 1/4
d) 0 :(-6,8)= 0
e) -3 3/5 x (-5/6)= -18/5 ×-5/6=3
f) -3 1/9 : (-4 2/3 )=-28/9 : -14/3=-28/9 × -3/14= 2/3
2009-12-13T10:58:59+01:00
A)-18:(-1/3)= 54
b)7,5 x (-1)= -7,5
c)-2,5 x 2 1/2= -6,25
d) 0 :(-6,8)= 0
e) -3 3/5 x (-5/6)= 3
f) -3 1/9 : (-4 2/3 ) = ⅔